Surviving social media : shut down the haters - Braun, Eric, 1971- (Informed! (North Mankato, Minn.), 2021)
Presents the beneficial and harmful effects of social media, and details the history of social media. Features strategies for managing online life, and includes color photographs, graphs, text-related questions, a timeline, a glossary, and additional resources.